Admission biomarkers among patients with acute myocardial-infarction related cardiogenic shock with or without out-of-hospital cardiac arrest an exploratory study. (3rd October 2021) - Thøgersen, Michael; Frydland, Martin; Lerche Helgestad, Ole Kristian; Okkels Jensen, Lisette; Josiassen, Jakob; Goetze, Jens Peter; Møller, Jacob Eifer; Hassager, Christian
Abstract: Background: Acute myocardial infarction complicated by cardiogenic shock (AMICS) with or without out-of-hospital cardiac arrest (OHCA) have some pathophysiological differences and could potentially be considered as two individual clinical entities. Thus, there may also be differences in terms of blood borne biomarkers. Purpose: To explore potential differences in concentrations of the biomarkers lactate, mid-regional proadrenomedullin (MRproADM), Copeptin, pro-atrial natriuretic peptide (proANP), Syndecan-1, soluble thrombomodulin (sTM), soluble suppression of tumorigenicity 2 (sST2) and neutrophil gelatinase-associated lipocalin (NGAL), in patients with AMICS with or without OHCA. Method: Patients admitted for acute coronary angiography due to suspected ST-elevation myocardial infarction were enrolled during a 1-year period. In the present study 86 patients with confirmed AMICS at admission were included. Results: In the adjusted analysis OHCA patients had higher levels of lactate (p = 0.008), NGAL (p = 0.03) and sTM (p = 0.011) while the level of sST2 was lower (p = 0.029). There was little difference in 30-day mortality between the OHCA and non-OHCA groups (OHCA 37% vs. non-OHCA 38%). Conclusion: AMICS patients with or without OHCA had similar 30-day mortality but differed in terms of Lactate, NGAL, sTM and sST2 levels. These findings support that non-OHCA and OHCA patients with CS could be considered as two individual clinical entities.